"Anterior subcutaneous pelvic internal fixator (INFIX), Is it safe?" A cadaveric study. Issue 10 (October 2016) - Apivatthakakul, T.; Rujiwattanapong, N.
Abstract: Introduction: Anterior pelvic internal fixator (INFIX) is used to treat unstable pelvic ring injuries. Nerve injury complications with this procedure have been reported. Objectives: This anatomic study attempted to identify structures at risk after application of INFIX. Materials and methods: INFIX was applied in fifteen fresh, frozen, anatomical specimens using polyaxial pedicular screws and subcutaneous rods. Surgical dissection was done to identify the structures at risk including the femoral nerve (FN), femoral artery (FA), femoral vein (FV) and the lateral femoral cutaneous nerve (LFCN) related to which are potentially affected by the implant. Results: All structures at risk were closer to the rod than to the pedicular screw. Measurements were made between the rod and the structures at risk. The LFCN was an average of 13.49 ± 1.65 mm (95% CI 12.871–14.103) from the lateral end of the rod. The FN was an average of 12.43 ± 3.42 mm (95% CI 11.151–13.709), the FA was an average of 12.80 ± 3.67 (95% CI 11.430–14.173) and the FV was an average of 13.48 ± 3.73 (95% CI 12.082–14.871) below the rod. No direct compression of the rod to the structure at risk was observed. Conclusions: The femoral nerve is the structure most at risk of compression by the INFIX rod. Careful surgical technique is required in every step of this surgery. We suggest using polyaxial screws and recommend that during screw insertion the surgeon should leave some space between the screw and rectus fascia. The the rod should be trimmed as short as possible to reduce LFCN irritation.